Mission possible : the Bbiblical strategy for reaching the lost - Ma, Julie C. (Oxford, UK : Regnum Books International, 2016)
Julie Ma's book is a refreshing and much needed return to first principles: this is God's world; reconciliation is God's work; self-giving service for others is God's way. Mission is possible precisely because it is God's mission, in God's world, undertaken by God's people, in God's way. What's more, God's mission is not only possible--its ultimate objective is inevitable!
The history of God's salvation -- Miacle in Papasok -- Light : a missiological reading -- Gentiles who associated with the people of God -- Power in mission -- Miracle accounts among the Kankana-ey Tribe -- Mission of Jesus in the Spirit (Luke 4) -- The Great Commission : church mandate -- The geographical expansion of the church in Acts -- Incarnational mission -- "Children, our children" -- Eschatology and mission -- The cross and mission.
JSTOR
Keywords: Missions -- Biblical teaching; Salvation -- Biblical teaching; Evangelistic work -- Biblical teaching; Missions -- Enseignement biblique; Évangélisation -- Enseignement biblique; Evangelistic work -- Biblical teaching; Missions -- Biblical teaching; Salvation -- Biblical teaching